2022
DOI: 10.3390/land11071008
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Sustainable Development of Traditional Ethnic Village Tourist Destinations: A Case Study of Jiaju Tibetan Village in Danba County, China

Abstract: In the process of development, traditional villages, as important tourism resources, have been impacted by external factors and lost their original authenticity. Looking for the important factors affecting its tourism development, in an attempt to assist the sustainable development of a rural destination, is Jiaju Tibetan Village in the Southwest of China. The sustainable evaluation index system divides the assessment criteria into five guideline layers: economic development, ethnic culture, management, sustai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Researchers have utilized a range of indicators and factors to evaluate the potential, such as economic factors, population distribution, environmental conditions, cultural aspects, infrastructure, and psychological factors [ 49 , 155 , 156 ]. Scholars have analyzed several aspects such as economic growth, ethnic culture, management practices, infrastructure and service facilities [164] to assess the impact of tourism on sustainable villages [ 157 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Researchers have utilized a range of indicators and factors to evaluate the potential, such as economic factors, population distribution, environmental conditions, cultural aspects, infrastructure, and psychological factors [ 49 , 155 , 156 ]. Scholars have analyzed several aspects such as economic growth, ethnic culture, management practices, infrastructure and service facilities [164] to assess the impact of tourism on sustainable villages [ 157 ].…”
Section: Resultsmentioning
confidence: 99%
“… The holistic perspective of traditional villages and rural tourism NO. Year Sub- topic Explanation Research method Primary Data source 84 2015 [ 155 ] Evaluating the Rural Tourism Potentials Analyze the strengths, weaknesses, opportunities, and threats of developing rural tourism from economic, social, cultural, and environmental aspects (Mixed) The Delphi method/SWOT analysis/the statistical data analysis Experts 85 2018 [ 156 ] (Mixed) The method of comparison/the experimental method/SWOT analysis The tourism sites owner/the rural tourism product users 86 2019 [ 56 ] (Quan) Questionnaire/SWOT analysis Inhabitants 87 2013 [ 160 ] (Mixed) Questionnaire/interview/Decision Making Trial and Evaluation Laboratory (DEMATEL) The experts 88 2022 [ 64 ] Sustainable development of the traditional village Assess the changes caused by tourism to assist the sustainable development of traditional villages from economic, environmental, cultural, social, and other aspects (Quan) questionnaire government officials/service providers/residents 89 2022 [ 158 ] (Mixed) Adaptive Cycle Theory/the entropy weight method Traditional villages 90 2022 [ 157 ] (Quan) Delphi expert scoring/AHP analysis/the statistical data analysis Experts 91 2017 [ 1 ] Revitalizing tradition...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the theory of heritage activation [ 7 ], when heritage resources are transformed into products without affecting the protection of heritage, the sustainable development of heritage will be achieved in the process of utilization. Relevant studies have shown that rural tourism is an effective way to activate traditional villages and promote rural revitalization [ 8 ]. However, the marginal and complex geographical characteristics of traditional villages [ 9 ] make communication with the outside inconvenient, resulting in poor spatial accessibility, which severely hinders village activation and utilization.…”
Section: Introductionmentioning
confidence: 99%
“…Scholars in the fields of archaeology and cultural studies focus on the value recognition of traditional villages, the reconstruction of village style, the inheritance of traditional village culture, and the protection and utilization of village cultural heritage [9][10][11][12]. The field of agricultural economics focuses on researching the agricultural development model, land use model, and sustainable development of rural economy in traditional villages [13][14][15][16]. The field of tourism mainly focuses on rural tourism, with research directions including the development and utilization of tourism resources in traditional villages, factors affecting the development of tourism in traditional villages, and the impact of tourism on the protection and development of traditional villages [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%